Public investment and poverty: the ecuadorian case up to 2020 - Bravo Placeres, Ismael (Revista Universidad de Guayaquil, 2019)
The present article examinesthe incidence of the public investment in the Ecuador. The analysis of the problem considers the situation of the poverty in the country, an I lash from growing proportions to global scale, especially in the last years. The analysis leaves of the literature officially published by the Ecuadorian government and the prosecution of secondary sources. The methodology used in the work is mixed, with support in the methods characteristic of the qualitative methodology for the documental analysis of works, rehearsals and articles referred to the different focuses and theories about the public investment and the poverty. The used data they are ofsecondary origin, because the statisticalinformation comesfrom institutionslike the National Institute of Statistic and Census (INEC), National Secretary of Planning and Development (SENPLADES), Integrated System of Knowledge and Social Statistic of the Ecuador (SiCES), National Plan for the Good one to Live (PNBV), among others.